Characteristic of Hemophilia A Patients in Initial Diagnosis in Dr. Soetomo General Hospital Surabaya - Angela Dinaria Kemala Swary; Mia Ratwita Andarsini; Arifoel Hajat (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: This research is conducted to describe the characteristic of Hemophilia A patients.Methods: Cross-sectional study conducted in 55 patients with Hemophilia A. The variables were age, bleeding episode, factor VIII level, and bleeding site. The data presented descriptively.Results: The largest group was 2-10 years old (52,73%). The most common bleeding episode occured in the patients was moderate level (60,0%). The most common patient’s factor VIII level was moderate level (52,7%). The patient’s bleeding most likely took place in muscle or known as hematoma (41,8%). While the less likely bleeding were intracranial and nose bleeding.Conclusion: 2-10 years old patient are the largest group because of hemophilia A mostly diagnosed in childhood, where children are actively moved so that the spontaneous bleeding or abnormal bleeding can be seen easily. Parents needs to be aware if there were abnormal or spontaneous bleeding which takes place in muscle or known as hematoma with moderate episode of bleeding which meant that the occurrence of spontaneous bleeding is periodically happened or in prolonged bleeding accompanied by minor trauma or invasive action.